Operational Interaction Framework for Enhancing Public Service Performance in Integrated Urban Transportation Systems - Agung Syukroni Pinandita; Onny Fitriana Sitorus; Camelia Safitri (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
The consistent implementation of public transportation services poses a significant governance challenge in rapidly growing metropolitan areas. Jakarta's integrated public transportation system, JakLingko, is expected to provide accessible, reliable, and responsive services to passengers. This study analyzes the implementation of public services on JakLingko Route 88 (Ancol Barat–Tanjung Priok Terminal) by proposing an operational mechanism that includes service provision, information delivery, and facility management, illustrating how policy objectives are translated into daily operations. While prior research has focused on service quality, passenger satisfaction, and collaborative governance, there has been limited exploration of the mechanisms underlying public service implementation in practice. Most studies assess service outcomes or governance structures but lack insight into how implementation occurs through interactions among operational actors and communication processes. This highlights the need for a process-oriented analysis of public service implementation at the operational level. Using a qualitative descriptive approach, data were collected through observations, in-depth interviews, and documentation from one operational manager, two drivers, and two passengers selected via purposive and snowball sampling. The analysis followed the interactive model of Miles, Huberman, and Saldaña, involving data condensation, display, and conclusion drawing. Findings reveal that effective public service implementation relies on the interaction between operational coordination, adaptive communication, and supporting facilities in response to dynamic urban traffic conditions. This study enriches the implementation perspective of Hill and Hupe and emphasizes the importance of adaptive coordination, integrated digital systems, and preventive facility management to enhance urban public transportation resilience.